2011
DOI: 10.1063/1.3660406
|View full text |Cite
|
Sign up to set email alerts
|

Low voltage vertical organic field-effect transistor with polyvinyl alcohol as gate insulator

Abstract: We report the preparation of low gate leakage current organic field effect transistors in vertical architecture using polyvinyl alcohol as gate insulator and C60 fullerene as n-type semiconductor in devices with gate, source, and drain electrodes of Al. Intermediate electrode and top electrode operate, respectively, as source and drain, or vice-versa, depending on polarity. In these devices the intermediate electrode (source or drain) is permeable to the electric field produced by the gate so that increased dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…The use of an ultra-thin metallic layer deposited through evaporation is one alternative that may fulfil these requirements [14]. Additionally, Rossi et al [7] and Seidel et al [8] have shown that the intermediate electrode resistance can be minimized by using additional metallic or polymeric layers, respectively. There are also strategies to produce electrodes with controlled permeability like the use of sphere-lithography [15e17], co-deposition of metal and organic molecules [18], atomic layer deposition assisted nanoimprint lithography [19], random network of metallic nanowires [20], C 60 -graphene vertical heterostructures [21] or use of blockcopolymer templates [9] to obtain improved ON/OFF ratio and lower operation voltage.…”
Section: Introductionmentioning
confidence: 98%
“…The use of an ultra-thin metallic layer deposited through evaporation is one alternative that may fulfil these requirements [14]. Additionally, Rossi et al [7] and Seidel et al [8] have shown that the intermediate electrode resistance can be minimized by using additional metallic or polymeric layers, respectively. There are also strategies to produce electrodes with controlled permeability like the use of sphere-lithography [15e17], co-deposition of metal and organic molecules [18], atomic layer deposition assisted nanoimprint lithography [19], random network of metallic nanowires [20], C 60 -graphene vertical heterostructures [21] or use of blockcopolymer templates [9] to obtain improved ON/OFF ratio and lower operation voltage.…”
Section: Introductionmentioning
confidence: 98%
“…The observed J DS was extremely high compared with those of other vertical-type organic transistors. [16][17][18][19][20][21][22][23][24][25][26] The gate current density (J G ) also increased with increasing V DS ; however, the observed J G was three orders of magnitude lower than J DS . Carriers cannot be injected in a gate electrode with increasing positive gate voltage unless the gate voltage exceeds the breakdown voltage.…”
mentioning
confidence: 99%
“…Several groups have reported vertical-type organic transistors such as polymer grid transistors, organic a Email: fukagawa.h-fe@nhk.or.jp b Present address: Tokyo University of Science, Suwa, 5000-1 Toyohira, Chino-city, Nagano, 391-0292, Japan c Present address: Tohoku University, 6-6-05 Aramaki Aza Aoba, Aoba-ku, Sendai, 980-8579, Japan d Present address: Yamagata University, Research Center for Organic Electronics, 4-3-16 Jonan, Yonezawa, Yamagata 992-8510, Japan static induction transistors (SITs), metal-base organic transistors (MBOTs), space-charge-limited transistors (SCLTs), patterned electrode vertical organic field effect transistor (PE-VOFET) and permeable-base transistor (PMBT) to realize a short channel. [15][16][17][18][19][20][21][22][23][24][25][26] However, the relationship between the crystalline axis of the organic film and the carrier transport direction has not been examined for vertical-type organic transistors. If the planar molecules are oriented with the molecular plane parallel to the substrate in a vertical-type organic transistor, the carrier transport direction can easily be aligned with the π-π stacking direction of the organic film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of various organic materials, poly (vinyl alcohol) (PVA) has also been introduced as a gate insulating layer for organic field-effect transistors to investigate a memory effect at high voltage (~80 V) (n-type small molecule), 31 a hysteresis trend (no memory study, p-type small molecule), 32 and a typical transistor performance (no hysteresis/memory effect). [33][34][35] However, no study has been reported on the influence of PVA molecular weights on the low-voltage operation and high retention stability of TOMDs with conjugated polymer channel layers.…”
Section: Introductionmentioning
confidence: 99%